The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1097/aog.0b013e318165f1a9
|View full text |Cite
|
Sign up to set email alerts
|

Social Factors Affecting Treatment of Cervical Cancer

Abstract: Health care in the United States has become a privilege rather than a right. Patients who have the greatest need are the ones most likely to be denied this privilege. Despite recent advances in disease detection and treatment, many patients do not receive even the bare minimum of care. The high complexity of the health care system in the setting of patients with low levels of health literacy significantly affects the ability to seek and receive treatment in a timely fashion. In addition, lack of insurance, tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 26 publications
0
15
0
3
Order By: Relevance
“…Residence near a treatment center is particularly crucial for disadvantaged individuals who may lack resources for travel owing to financial constraints and other unquantifiable obstacles. 12,13 Disease recurrence was highest in African Americans, with 50% of these patients recurring at a median of 12.33 months (range, 8.97Y17.97 months). This finding is consistent with previous studies, which demonstrated that mortality from cervical cancer is significantly higher in African Americans than in Caucasians.…”
Section: Discussionmentioning
confidence: 99%
“…Residence near a treatment center is particularly crucial for disadvantaged individuals who may lack resources for travel owing to financial constraints and other unquantifiable obstacles. 12,13 Disease recurrence was highest in African Americans, with 50% of these patients recurring at a median of 12.33 months (range, 8.97Y17.97 months). This finding is consistent with previous studies, which demonstrated that mortality from cervical cancer is significantly higher in African Americans than in Caucasians.…”
Section: Discussionmentioning
confidence: 99%
“…Pour les femmes les moins diplômées, le risque de mortalité est multiplié par 1,8 comparé à celui des femmes les plus diplômées. Pour le cancer broncho-pulmonaire et les cancers de l'utérus, le risque est supérieur pour les femmes les moins diplômées [6], cela peut être lié au tabagisme et aux pratiques sexuelles plus précoces comme cela a été montré dans le cancer du col utérin dans des études internationales [12][13][14]. Au contraire, les femmes les plus diplômées ont un risque de cancer du sein supérieur à celui des femmes les moins diplômées.…”
Section: éPidémiologieunclassified
“…This will also help to increase the health literacy on cervical cancer risk factors, symptoms and how to access relevant services in the community. Studies have supported the value of health literacy in improving the ability of women with cervical cancer to seek and receive treatment in a timely fashion 16 . …”
Section: Education Of Women On the Disease To Improve Their Health Sementioning
confidence: 99%
“…Leaving individuals to bear the cost for such lifesaving preventive and therapeutic services, implicitly limits the utilization of cervical cancer services which could contribute to the late presentation in advanced stages with dismal survival probability. Even in developed societies were treatment facilities are available, cost related factors, health insurance, low levels of health literacy, lack of social support and transportation barriers have limiting effects on patients receiving care in a timely fashion 4,[13][14][15][16][17] . It is therefore imperative to look closely at the options for improving cervical cancer health outcomes in Nigeria and similar settings in Africa in the perspective of societal rather than individual investments.…”
Section: Societal Investment and Cervical Cancer Outcomesmentioning
confidence: 99%